2018
DOI: 10.1111/1348-0421.12594
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of hemagglutinin protein of measles viruses in Hokkaido district, Japan, 2006–2015

Abstract: Strains of measles virus of genotypes D5, H1, D4, D8, and B3 were detected among epidemic, endemic, imported and import-associated cases in Hokkaido district, Japan, during 2006-2015. In the present study, their antigenic features were evaluated by determining the complete nucleotide sequences of their hemagglutinin proteins, which are a major target for neutralizing antibodies, and their amino acid sequences deduced. It was found that the hemagglutinin proteins of these strains had several novel amino acid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Mutations of H448R and K460R in B3 strains were found in this study which may lead to increasing the interaction with CD46. Luca Perabo demonstrated that arginine cause to restore the binding receptor ability ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of H448R and K460R in B3 strains were found in this study which may lead to increasing the interaction with CD46. Luca Perabo demonstrated that arginine cause to restore the binding receptor ability ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%